2021
DOI: 10.1088/1755-1315/883/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Estimation rumen degradable protein of local feeds in dairy cattle using in sacco method

Abstract: There is a lack of nutrition information on local feeds protein in Indonesia, especially to determine protein fraction of dairy feed. The objective of this study was to determine rumen degradable protein (RDP) of local feeds in dairy cattle using in sacco method. The local feeds are copra meal, palm kernel meal, coffee husk, tofu waste, soy-sauce waste, brewer waste, and habbatussauda waste. Two ruminal fistulated male Frisian Holstein were used to determine rumen degradable protein using in sacco method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Some forage and roughage usually used in tropical areas were Napier grass, natural grass, corn leaves, corn husk, and rice straw (Despal et al 2020). While the concentrated raw materials frequently used were copra meal, palm kernel meal, coffee husk, tofu waste, soy-sauce waste, brewer waste, and habbatussauda waste (Rosmalia et al 2021). High lignocellulosic roughage such as rice straw and corn husk are frequently used to substitute fresh forage, especially during the dry season when the forages grow slower.…”
Section: Introductionmentioning
confidence: 99%
“…Some forage and roughage usually used in tropical areas were Napier grass, natural grass, corn leaves, corn husk, and rice straw (Despal et al 2020). While the concentrated raw materials frequently used were copra meal, palm kernel meal, coffee husk, tofu waste, soy-sauce waste, brewer waste, and habbatussauda waste (Rosmalia et al 2021). High lignocellulosic roughage such as rice straw and corn husk are frequently used to substitute fresh forage, especially during the dry season when the forages grow slower.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the particle size used must be larger than the pore size. Rahmat et al [9] used a 5 mm forage particle size, while Rosmalia et al [10] used 2 mm for concentrate. The 1 mm (1000 microns) feed particle used in the study was larger than the pore size of the fabric (50-100 microns), preventing undigested feeds from spilling out of the bags.…”
Section: Hole Numbermentioning
confidence: 99%
“…Consequently, in situ can be the choice to determine feedstuff degradation. Orskov and McDonald [8] developed the in situ method and used different incubation times, enabling researchers to study the fermentation kinetics of feeds in the rumen [9,10]. It was possible to study feed digestibility by incubating feed in the rumen using this method.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the RDP of SBM and SS were 66.0% and 76.0%, respectively [3,4]. High protein content in feedstuff is correlated with high RDP levels [5]. SBM and SS containing protein with high biological value and RDP levels might lead to excessive ammonia concentration in the rumen, therefore it needs to be protected to increase protein utilization.…”
Section: Introductionmentioning
confidence: 99%